Not at the table but stuck paying the bill: perceptions of injustice in China's Xin'anjiang eco-compensation program. Issue 6 (2nd November 2022) - Jiang, Xinhui; Eaton, Sarah; Kostka, Genia
ABSTRACT: A growing body of research highlights the decisive role that justice claims play in creating sustainable payment for ecosystem services (PES) programs. Employing Sikor et al.'s approach to the study of justice claims in ecosystem governance along three dimensions—distribution, procedure and recognition—we study the negotiation process behind China's flagship interprovincial PES agreement: the Xin'anjiang River eco-compensation agreement between Huangshan (Anhui province) and Hangzhou (Zhejiang province) prefectures. We find that divergent claims between stakeholders on matters of distributive and procedural justice undercut one party's commitment to the agreement. Local officials in the upstream locality (Huangshan) see themselves as having been disadvantaged in both procedural and distributive aspects of negotiation. They claim to have been insufficiently included in a bargaining process that involved not only the downstream locality (Hangzhou) but also the central government. Huangshan stakeholders also see themselves as largely excluded from the benefits of cleaner water and bearing too much of the pollution abatement cost. For their part, Hangzhou stakeholders have advanced a 'polluters pay' view of distributive justice and found partial support for this claim from Beijing. Our findings suggest that attending to environmental justice considerations should be given top priority in China's design of PES schemes.